Reading Of Surat Al-Fatihah In The Tawasul Tradition At Pesantren Nurul Jadid - Lukman Sholeh; Ahmad Barizi; Durrotul Masruroh (Aafiyah: Jurnal Multidisiplin Ilmu, 2024)
This study aims to describe the tawasul tradition in the Nurul Jadid Islamic Boarding School Paiton Probolinggo. This research approach is descriptive qualitative type. The research subjects comprised the caretaker of the Nurul Jadid Islamic Boarding School and the head of the Nurul Jadid Islamic Boarding School. The collection technique uses interviews, documentation, observation, and data analysis techniques using data reduction, data presentation, and conclusion. The results show that the tawasul tradition in Islamic boarding schools has several meanings in reading tawasul in Islamic boarding schools 1. Means of praying, 2. Means to connect scientific sanad, 3. Means to connect spiritual sense, 4. Media for dhikr to others. Allah, 5. Increase love for Allah. While the benefits of reading tawasul on students' personalities in Islamic boarding schools 1. They were becoming a person who likes to be grateful, 2—being patient, 3. Being calm, 4. They respect people, 5. Being a person who wants to give and be generous, 6. Be happy with Allah's destiny